PLACEMAKING IN TANAH ABANG: BETWEEN DIMENSIONS AND INTENSITY OF PEDESTRIAN WAYS - Kariza Ayu Gayatri Sukasta; maria Immaculata Ririk winandari (International Journal on Livable Space, 2020)
ABSTRACT Placemaking in pedestrian ways of a commercial area has its own characteristics, especially between central mode of transportation and shopping center. The area between Tanah Abang Station and “Blok A” Tanah Abang Market is bustling with variety of activities, especially temporary commercial activities by street vendors and hawkers as a form of placemaking. This paper explores the relationship between road dimensions and pedestrian intensity of placemaking that occurs along the pedestrian ways between the station and Blok A of The Market. The research method used is mixed method of quantitative data processing and qualitative analysis. Variables used include the dimensions of the pedestrian ways and pedestrian intensity on the path. Pedestrian ways’ dimensions cover the width and length of the pathway. Pedestrian intensity is measured by the amount, speed, and space of the pedestrian. Case studies include pedestrian ways on four streets, namely the Streets of Jatibaru Raya, Kebon Jati, Jatibaru 2, and Jatibaru 10. The results of the study show that all four streets have similar placemaking although they differ in dimensions and intensity. This shows the relationship between the dimensions of the road with the intensity of the road and it does affect the formation of place/placemaking. The narrower the width of the road and the shorter the length of the road, the higher the intensity of pedestrians, which is an indicator of the formation of placemaking in the pedestrian ways of Tanah Abang. Keywords: pedestrian way dimensions, pedestrian intensity, placemaking